Long-term stability of the toroidal current measurement at JET using fibre optics current sensor. (1st April 2022) - Gusarov, A.; Leysen, W.; Beaumont, P.; Boboc, A.; Wuilpart, M.; Dandu, P.; Croft, D.; Bekris, N.; Batistoni, P.; ,
Abstract: The Fibre Optic Current Sensor (FOCS) is a system that will perform plasma current measurements at ITER during long plasma discharges under intense nuclear radiation. These measurements are important for safe machine operation. The FOCS must perform well in a harsh tokamak environment, which include strong magnetic fields, high temperatures, and also significant levels of neurons and high energy photons. JET is a unique machine where the impact of such conditions on the sensor performance can be investigated experimentally in representative conditions. In this work we analyse stability of the fibre Verdet constant using data obtained with two polarisation detection based FOCS systems installed at JET and operated in various machine scenarios with currents up to 4.2 MA. Analysis of data accumulated during more than four years demonstrates that long-term Verdet constant's changes are less than 0.5%. However, on a month time scale, windows with deviations up to ±9% from the average value are observed. The reason for these windows is unknown at the moment and will be studied in a future.